PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERGAMBAR KARTUN PADA MATERI BANGUN DATAR UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR SISWA KELAS III SEKOLAH DASAR - Yolanda, Nela Sari (RC-INSTITUT, 2018)
This study has the aim to increase the interest and learning outcomes of third grade elementary school students towards mathematics, especially on flat-build material. The aim to be achieved from this development effort is to produce a valid, practical and effective LKS. The development of cartoon drawings worksheets in this study uses the Instructional Development Institute (IDI) procedural model that applies the principles of a system approach, namely define or analyze needs, develop and evaluate. LKS validation is carried out by experts in mathematics education and Indonesian language education. The results of the study showed that the cartoon worksheet on the flat-building material was valid in terms of content and construct. Keywords:  LKS, Cartoon Drawings, Flat Build, Validity